END OF LIFE AND QUALITY OF LIFE IN OLDER ADULTS WITH ADVANCED CANCER: A QUALITATIVE ANALYSIS WITH CAREGIVERS. (11th November 2018) - Moss, K; Douglas, S; Daly, B; Lipson, A; Blackstone, E
Abstract: The number of families caring for older adults continues to increase. Caregivers are challenged to address personal healthcare needs, their desires for their loved one, as well as their loved one's wishes for themselves, while struggling to interpret the language of healthcare. The purpose of this study was to examine understanding of quality-of-life, end-of-life, and decision-making terminology among caregivers of older adults with advanced cancer. Interviews were conducted with nine caregivers of older adults (≥ age 55) with advanced cancer, a sub-sample from a longitudinal, descriptive, correlational study (NRO14856). Interviews were audio recorded and transcribed. Content analyses were conducted and guided by Miles and Huberman's analysis methods. Most caregivers were female caring for a spouse. Healthcare decision making most often involved the patient and caregiver with heavy reliance on guidance from oncologists and nurses. Most caregivers were familiar with the term 'hospice, ' but, the term 'palliative care' was either unfamiliar, or the definition was not known. Caregivers expressed emotions and discussed anxiety related to decision making as significant. Most caregivers described their own quality of life, as well as their loved one's, as good or high. The 2016 National Institutes of Sciences, Engineering and Medicine report entitled Families Caring for an Aging America highlights the importance of engaging family caregivers in decision making. This study provides exemplars of shared decision making between the patient, caregiver, and healthcare providers. Creative solutions are needed for improvements in palliative care education to assist older adults and caregivers in making more informed healthcare decisions.